STEGANOGRAFI DUAL METHOD PADA SINYAL AUDIO - , Shinta Estri Wahyuningrum; , Dr.-Ing. Mhd. Reza M. I. Pulungan, S.Si., M.Sc., ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In exchanges of information, it is often necessary to guarantee confidentiality and security during data transmission process. Ensuring the safety of the sending process becomes very important. Steganography technique that is: hide the message by using media other files, can be image files or audio files to an alternative message concealment. Some methods steganography that has developed in audio media, for examples: Silence Interval Length (SIL) Method, the message was hidden with change the length of the part of audio signal was named silence interval. The other method is Modified Least Significant Bit (MLSB), in this method the message was hidden by changing the value of LSB on the signal audio with one bit from message. The value that used in MLSB method are 255 and 254. This study attempted to analyze the successful implementation of steganography methods with SIL and MLSB on the an audio signal. Simple system built to test: both of method can be used together on a signal audio, system performance , and robustness with MP3 compression of both methods. The results show that SIL and MLSB method can be used simultaneously on an audio file, while in the resilience, these two methods are not resistant to the MP3 compression process.